Estudo experimental e numérico de uma antena ressoadora dielétrica baseada em CaTi 1-x (Nb 2/3 Li 1/3) xO3-δ (CNLTO) e CaTi 1-x (Nb 1/2 Ln 1/2)xO3 (Ln=Bi (CNBTO) e Fe(CNFTO)) para aplicações em bluetooth - Costa, Rodrigo Carvalho Souza (2007)
The progress of telecommunication industry is highly dependent of the fabrication of low cost, quality factor and smaller size of the individual components for commercial applications. This kind of characteristics are necessary to warranty that the signal have well suited frequency, avoiding the noise interference signals, that could affect the performance of the telecommunication systems. Dielectric ceramics have significant advantages of light weight, low cost, small size, low profile, high radiation eficiency, low production cost and ease of integration with other active or passive microwave integrated circuit. This work will provide a new ceramic material that could be used in a miniature antenna for Bluetooth applications. This work is divided in three stages. The first one is develop a new material with a good dielectric permittivity (25 < ²r < 50), high quality factor (Q > 5000) and low temperature coeficient of resonant frequency (¿f ). The second one characterize the developed material by XDR, Raman, Infrared and dielectric spectroscopy in microwave region. The last one is build and simulate the antenna made with the developed dielectric material.